Isolation and Identification of Optochin-Resistant Viridans Group Streptococci from the Sputum Samples of Adult Patients in Jakarta, Indonesia - Wisiva Tofriska Paramaiswari; Nurma Sumar Sidik; Miftahuddin Majid Khoeri; Wisnu Tafroji; Wahyu Finasari Said; Dodi Safari (International Journal of Microbiology)
Aim. To investigate optochin-resistant viridans group streptococci (VGS) strains isolated from the sputum sample of adult patients with different clinical symptoms. Materials and Methods. Optochin-resistant VGS isolates were identified by matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS). recA sequencing was used to confirm identified isolates at the genus level by MALDI-TOF MS. Finding. We identified 79% of tested isolates (148/187) at the species-level identification using the MALDI-TOF MS tool. We identified that the most common species isolated from sputum specimens were S. oralis (44.9%) followed by S. mitis (25.7%), S. infantis (9.1%), S. parasanguinis (7.5%), S. peroris (3.7%), S. anginosus (2.7%), and S. sanguinis (2.1%). Discussion. The S. oralis strains were majority of optochin-resistant VGS isolates obtained from sputum of adult patients in Jakarta, Indonesia. MALDI-TOF MS showed potential for the rapid identification tool to identify optochin-resistant VGS isolates. Although there were discrepancies in identifying isolates at the genus/species level, the performance could be improved by expanding its database.